1987
DOI: 10.1097/00000658-198712000-00015
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Percutaneous Angioplasty in the Management of Chronic Hemodialysis Fistulas

Abstract: One hundred forty-one dilatations of stenotic lesions in dialysis access fistulas were performed. The initial success rate was 82%. The one-year patency rate was 45%, with a 2-year patency rate of 24%. Best results were obtained with a discrete stenosis at a graft-to-vein anastomosis. The procedure can be done on an outpatient basis and, although long-term results are poor, in appropriate patients multiple dilatations can be performed to keep a fistula functioning for many years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
58
0
7

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(67 citation statements)
references
References 11 publications
2
58
0
7
Order By: Relevance
“…Having shown a three-fold adjusted relative risk for restenosis after PTA by comparison with surgery, our study confirms the results of previous noncomparative studies that reported higher primary patency rates in surgical series than after dilation in failing forearm AVF (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)25,26,28). Moreover, the unadjusted 1-yr primary patency rates in our series (91 Ϯ 6% for surgery and 54 Ϯ 8% for PTA) compare favorably with the literature, which reports rates of 64 to 88% after preemptive surgery (12,19,25,26) and 16 to 79% after endovascular procedures (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Having shown a three-fold adjusted relative risk for restenosis after PTA by comparison with surgery, our study confirms the results of previous noncomparative studies that reported higher primary patency rates in surgical series than after dilation in failing forearm AVF (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)25,26,28). Moreover, the unadjusted 1-yr primary patency rates in our series (91 Ϯ 6% for surgery and 54 Ϯ 8% for PTA) compare favorably with the literature, which reports rates of 64 to 88% after preemptive surgery (12,19,25,26) and 16 to 79% after endovascular procedures (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the unadjusted 1-yr primary patency rates in our series (91 Ϯ 6% for surgery and 54 Ϯ 8% for PTA) compare favorably with the literature, which reports rates of 64 to 88% after preemptive surgery (12,19,25,26) and 16 to 79% after endovascular procedures (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In addition, restenosis rates after the two surgical techniques were similar in our study, failing to support the concern of any higher complication rates' being associated with the PTFE interposition graft (24).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Although PTA is effective in treating stenotic lesions in dialysis fistulas, its benefit could be attenuated by a high restenosis rate within 6 mo. 10,11 The mechanisms of restenosis in arterial systems have been widely investigated; however, direct application of these mechanisms to the venous segment of AVFs may not be valid. At the anatomic level, veins tend to have a less well-defined internal elastic lamina.…”
Section: Discussionmentioning
confidence: 99%